Senses of the being-there-woman-after-cardiac-surgery supported by Heidegger - Thaís Vasconselos Amorim; Anna Maria de Oliveira Salimena; Maria Carmen Simões Cardoso de Melo; Ívis Emília de Oliveira Souza; Lúcia de Fátima da Silva (Universidade Federal do Ceará, 2013)
Qualitative study aimed at presenting the unveiling of the senses of the being-there-woman-after-cardiac-surgery supported by Heidegger´s referential. The setting was a hospital accredited for performing highly complex cardiovascular procedures in Minas Gerais, Brazil. The field stage occurred in December 2011 and January 2012, and the subjects interviewed from the following question: How is your day-by-day after the cardiac surgery? The readings and recorded speeches enabled a comprehensive analysis and interpretation. It was learned that the woman shown in publicity, dominated by impersonal behavior in their speeches, curiosity and ambiguity. That reveals the inadequacy in the fear facing horror and terror, towards decadence. Facing the existential procedures, one can understand that as a being-in-the-world, the woman covered herself with the will to take care of herself, pointing a gap to be filled by the nurses through health promotion which should be in their practice.